Strategi Komunikasi Politik Pemerintahan Daerah dalam Meningkatkan Partisipasi Masyarakat Pedesaan (Studi pada Desa Karangsari Kec. Bantur Kab. Malang) - Suryaningsih Silalahi; Julia Ivanna (Journal on Education, 2024)
This research aims to analyze the political communication strategies implemented by regional governments to increase participation in rural communities, especially in Karangsari Village, Bantur District, Malang Regency. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews, observation and documentation. The research results show that the Karangsari Village government uses various communication strategies, including direct outreach, use of local media, and community forums. This strategy has succeeded in increasing community awareness and participation in various village development programs. The key factors that support the success of this strategy are community trust in village leaders, openness of information, and active involvement of various stakeholders. This research provides important insights for other local governments in designing and implementing effective political communication strategies to increase rural community participation.